Screening and preservation application of quorum sensing inhibitors of Pseudomonas fluorescens and Shewanella baltica in seafood products. (September 2021) - Wang, Yanbo; Wang, Yongzheng; Chen, Jian; Koseki, Shigenobu; Yang, Qing; Yu, Hejun; Fu, Linglin
Abstract: Pseudomonas fluorescens and Shewanella baltica are specific spoilage organisms (SSOs) of most seafood products. Both of them can cell-to-cell communicate through quorum sensing (QS), facilitating the spoilage activities such as protease secretion, flagellar movement, and biofilm formation. Thus, it is important to screen the quorum sensing inhibitors (QSI) of P. fluorescens and S. baltica. In this study, we tried to apply a high-throughput virtual screening technology to select QSIs candidates. Three amino acid sequences from the key QS regulator–LuxR/I family (the LuxR and LuxI proteins of P. fluorescens, and the LuxR of S. baltica ) were targeted and analyzed . Their 3D structures were subsequently constructed for the QSIs candidates' screen of both P. fluorescens and S. baltica . The candidates of cytidine-5′-monophosphate (5′-CMP) and 5′-adenylic acid (5′-AMP) with high scores exerted strong antagonistic effects against both P. fluorescens and S. baltica QS. The addition of 5′-CMP and 5′-AMP also inhibit QS-controlled phenotypes (swimming motility, protease activity, EPS, and biofilm formation) in P. fluorescens and S. baltica . Furthermore, the exogenous addition of 5′-CMP and 5′-AMP could retard the spoilage process of salmon slices during low-temperature storage by inhibiting the production of extracellular protease, siderophores, and Total Volatile Basic Nitrogen (TVB-N). Highlights: A natural compound library was constructed for quorum sensing (QS) inhibition. Cytidine-5′-monophosphate (5′-CMP) and 5′-adenylic acid (5′-AMP) was selected. QS systems in P. fluorescens and S. baltica were inhibited by 5′-CMP and 5′-AMP. 5′-CMP and 5′-AMP interfered with QS-regulated phenotypes. Exogenous addition of 5′-CMP and 5′-AMP extended the shelf-life of salmon slices.